Developing energy efficient lignin biomass processing: towards understanding mediator behaviour in ionic liquids - Eshtaya, Majd; Ejigu, Andinet; Stephens, Gill; Walsh, Darren A.; Chen, George Z.; Croft, Anna K. (Royal Society of Chemistry, 2016)
Environmental concerns have brought attention to the requirement for more efficient and renewable processes for chemicals production. Lignin is the second most abundant natural polymer, and might serve as a sustainable resource for manufacturing fuels and aromatic derivatives for the chemicals industry after being depolymerised. In this work, the mediator 2,2′-azino-bis(3-ethylbenthiazoline-6-sulfonic acid) diammonium salt (ABTS), commonly used with enzyme degradation systems, has been evaluated by means of cyclic voltammetry (CV) for enhancing the oxidation of the non-phenolic lignin model compound veratryl alcohol and three types of lignin (organosolv, Kraft and lignosulfonate) in the ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate, ([C2mim][C2SO4]). The presence of either veratryl alcohol or organosolv lignin increased the second oxidation peak of ABTS under select conditions, indicating the ABTS-mediated oxidation of these molecules at high potentials in [C2mim][C2SO4]. Furthermore, CV was applied as a quick and efficient way to explore the impact of water in the ABTS-mediated oxidation of both organosolv and lignosulfonate lignin. Higher catalytic efficiencies of ABTS were observed for lignosulfonate solutions either in sodium acetate buffer or when [C2mim][C2SO4] (15 v/v%) was present in the buffer solution, whilst there was no change found in the catalytic efficiency of ABTS in [C2mim][C2SO4]–lignosulfonate mixtures relative to ABTS alone. In contrast, organosolv showed an initial increase in oxidation, followed by a significant decrease on increasing the water content of a [C2mim][C2SO4] solution.